COVID-19 and the global energy market: implications for international and domestic policies in the Arab Gulf states. Issue 4 (1st November 2020) - Wright, Steven
Abstract : For the Gulf states, the COVID-19 pandemic has acted as an accelerant to systemic fiscal challenges the states were projected to face. These longer-term fiscal challenges were a result of fundamental shifts in the global energy market towards lacklustre demand, oversupply of oil and gas, and depressed prices. Moreover, the shift towards carbon -neutrality and investment in renewables by key regions such as the European Union and China, have added to the long-term outlook on fossil fuel demand. This article examines such trends and concludes that the Gulf region is facing a looming fiscal cliff, whereby public policy within the Gulf states will necessarily reflect the three main areas of taxation, austerity and increased activity in the bond market to raise liquidity. Such trends have been made more pronounced by the pandemic. It is argued that in the context of rising debt, the immediate challenge identified for these states will be their peg to the United States Dollar. Such fiscal conditions will necessitate a drive by these states to attract foreign direct investment, and greater engagement with China through the Belt and Road Initiative is identified as a likely outcome. Therefore, this article concludes that the impact of the pandemic will hasten a shift in both public policy, state-society-relations, and in the international relations of the region.